2018
DOI: 10.1038/s41395-018-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection Does Not Protect Against Eosinophilic Esophagitis: Results From a Large Multicenter Case-Control Study

Abstract: H. pylori infection was not inversely associated with EoE, neither in children nor in adults. A borderline inverse association was confirmed for atopy and allergic rhinitis, but not asthma of food allergy. Our findings question a true protective role of H. pylori infection against allergic disorders, including EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 35 publications
1
37
1
2
Order By: Relevance
“…Therefore, the current eradication protocol will not bring adverse consequences commonly associated with antibiotic use, such as obesity, gastroesophageal reflux disease, irritable bowel disease, or allergic asthma. Some studies have suggested that H. pylori has a protective effect on eosinophilic esophagitis, but more recent studies have more or less debunked this notion …”
Section: Helicobacter Pylori Eradication and Gastric Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the current eradication protocol will not bring adverse consequences commonly associated with antibiotic use, such as obesity, gastroesophageal reflux disease, irritable bowel disease, or allergic asthma. Some studies have suggested that H. pylori has a protective effect on eosinophilic esophagitis, but more recent studies have more or less debunked this notion …”
Section: Helicobacter Pylori Eradication and Gastric Cancer Preventionmentioning
confidence: 99%
“…Some studies have suggested that H. pylori has a protective effect on eosinophilic esophagitis, but more recent studies have more or less debunked this notion. 35…”
Section: Helicobacter Pylori Eradication and Gastric Cancer Preventionmentioning
confidence: 99%
“…They are considered to be caused by chronic allergic reactions to various allergens, including food and environmental antigens. The pathogenesis of EoE has yet to be completely elucidated, with both genetic and environmental factors considered to be involved [ 20 , 21 , 22 ]. In case of EoE, medical therapies consist primarily of oral proton pump inhibitors, elimination diet or orally administered topical corticosteroids, whereas immunosuppressive or immunomodulatory drugs, such as systemic corticosteroids and biologic therapies, are more frequently prescribed in patients with EGE or EC [ 6 , 7 , 8 , 19 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large prospective multicenter case‐control study was conducted in Spain, Italy, France, and Colombia (N = 808), in order to investigate a possible association between H pylori infection and eosinophilic esophagitis (EoE) . No significant difference in the prevalence of H pylori infection was identified between cases and controls in children (42% vs 46%), questioning an inverse association of H pylori and EoE.…”
Section: Clinical Presentationmentioning
confidence: 99%